Middle English Manuscripts and their Legacies
1 online resource.
Keywords: This volume celebrates and extends the extraordinary and transformative work of Ian Doyle on medieval manuscripts and their legacies. Eighteen original contributions by eminent international scholars of manuscript studies and history of the book present new research on textual issues, manuscript preservation and circulation, manuscripts and print, and the afterlives of manuscripts. Essays adopt the multi-faceted and nuanced approaches to manuscript studies and history of the book characteristic of Ian Doyle's work, taking up topics to which his research has drawn attention, extending his studies of particular manuscripts, scribes and networks, and exploring his remarkable contributions to the field. Contributors are: Ralph Hanna, Susan Powell, Julia Boffey, David Rundle, James Willoughby, Carol Meale, Martha Driver, William Marx, Veronica O'Mara, Richard Gameson, Kathleen Scott, Margaret Connolly, Richard Beadle, A. S. G. Edwards, Elizabeth Rainey, Pamela Robinson, Toshi Takamiya, Linne Mooney, and Derek Pearsall.